Kategori Unggulan di Provinsi Sumatera Selatan Pasca Covid-19 dan Pengelompokan Kabupaten Kota Menggunakan K-Means Clustering - Lismiana, Lismiana; Tanur, Erwin; Uli Sitanggang, Yuliana Ria (Publikasi Penelitian Terapan dan Kebijakan, 2023)
Determining the leading sector is very important as a basis for policy making to improve the economy of a region. This research aims to identify leading sectors before and after the Covid-19 pandemic in South Sumatra using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), Klassen Typology Analysis and Shift Share methods. This research groups districts/cities based on their GRDP contribution using K-Means Clustering. This research shows that the leading sectors before the pandemic were Mining; Water Supply, and Real Estate. During the pandemic, the contribution of agriculture actually increased from the previous year. So after the Covid-19 pandemic occurred, the Agriculture, Mining and Real Estate categories became the leading sectors. Grouping districts/cities produces three clusters. The cluster that has the lowest GRDP contribution is in cluster 1 with 14 members from 17 districts/cities in South Sumatra, the cluster that has the very highest GRDP contribution is in cluster 2 with 1 district/city and the rest with high GRDP contributions are in cluster 3 as many as 2 districts/cities. The agricultural category is the basic and prospective category for 64 percent of members in cluster 1. The government should prioritize increasing leading sectors, especially agriculture, to boost the economy in South Sumatra Province.